2014
DOI: 10.1177/0265407514524848
|View full text |Cite
|
Sign up to set email alerts
|

Navigating romantic relationships on Facebook

Abstract: The present study explores how people use social networking sites to adjust to breakups by studying their postdissolution behaviors. We apply Rollie and Duck’s (2006) relationship dissolution model by examining how collegiate Facebook users ( N = 208) enact behaviors in breakups to extend the model to online environments during and after breakups. Furthermore, we employed a retrospective design utilizing qualitative methods to define categories of behavioral responses to a breakup on Facebook. The analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…They often share updates or pictures with a hidden reference to their lives accordingly the real meaning of the featured content is not evident for every acquaintance, but it is for a selected few, e. g. the closest friends or the (previous) romantic partner (Marwick and Boyd 2014). Our findings are analogous with previous studies (Fox et al 2014;LeFebvre et al 2015;Ouytsel et al 2016), that is Instagram clearly have a different function in users' personal life depending on their relationship status. Finally, the qualitative research pointed out that Instagram has a definite impact on offline routines and habits.…”
Section: Discussion Of Studysupporting
confidence: 84%
See 1 more Smart Citation
“…They often share updates or pictures with a hidden reference to their lives accordingly the real meaning of the featured content is not evident for every acquaintance, but it is for a selected few, e. g. the closest friends or the (previous) romantic partner (Marwick and Boyd 2014). Our findings are analogous with previous studies (Fox et al 2014;LeFebvre et al 2015;Ouytsel et al 2016), that is Instagram clearly have a different function in users' personal life depending on their relationship status. Finally, the qualitative research pointed out that Instagram has a definite impact on offline routines and habits.…”
Section: Discussion Of Studysupporting
confidence: 84%
“…Users typically tend to change their online behaviour after a break-up. Previous studies found that users can be not just up to date regarding the expartner's everyday life through social media, but they also can address them indirect messages, e. g. posts which have a hidden meaning interpretable by only the previous partner (Marwick and Boyd 2014;LeFebvre et al 2015;Ouytsel et al 2016). Ergo, monitoring of the ex-partner's online activity and indirect communication towards social media platforms are important (new) functions of social media after a break-up which implies notable changes in the characteristics of SNS use.…”
Section: Connections Between Instagram Use and Romantic Relationship mentioning
confidence: 99%
“…Monitoring is referred to as “Facebook stalking” or “creeping” in colloquial nomenclature and is so common that this monitoring behavior is described as normal among young adults (Fox & Tokunaga, 2015; Lukacs & Quan-Haase, 2015). Although monitoring on Facebook is used to reduce relational uncertainty in romantic relationships (Fox & Anderegg, 2014), it can also prompt jealousy (LeFebvre, Blackburn, & Brody, 2015; Muise, Christofides, & Desmarais, 2009).…”
Section: Romantic Relationship–oriented Facebook Behaviorsmentioning
confidence: 99%
“…Millions of people log in on a daily basis to connect and share their lives through photos and posts (e.g., Duggan, 2015). The accessibility of information on SNS influences relationship development over time, aids in relationship maintenance, displays relationship dissolution, and reveals the multimodality of information between (online and offline) relationships (Dainton, 2013; Fox, Warber, & Makstaller, 2013; LeFebvre, Blackburn, & Brody, 2015). Indeed, researchers (e.g., Walther, 2011) have put forth a call to examine how online behaviors reflect different relationship stages.…”
mentioning
confidence: 99%
“…For instance, 72% of online adults use Facebook (Duggan, 2015). Previous relational researchers have investigated how individuals initiate and certify their relationships as “official” (Fox et al, 2013), how partners maintain their relationships (Dainton, 2013; Tong & Walther, 2011), and how individuals enact breakup processes (LeFebvre et al, 2015) all via Facebook. However, despite the proliferation of research into the link between SNS use and relational behaviors, little information is known about the specific behaviors individuals engage in throughout the relationship lifespan (i.e., escalation to de-escalation).…”
mentioning
confidence: 99%